Highly Discriminating Photorelease of Anticancer Drugs Based on Hypoxia Activatable Phototrigger Conjugated Chitosan Nanoparticles. (7th February 2013) - Lin, Qiuning; Bao, Chunyan; Yang, Yunlong; Liang, Qiannan; Zhang, Dasheng; Cheng, Shuiyu; Zhu, Linyong
<x xml:space="preserve">Abstract</x> An ultimately selective photorelease system of chitosan‐nanoparticles is constructed. Only under unique aspects of tumor‐hypoxia physiological conditions, the preliminary locked phototrigger is unlocked by biological reduction to enable the release of the caged drug either by visible light or two‐photon near‐IR (NIR) excitation. This approach provides a highly discriminating photorelease of anticancer drug to hypoxic tumor cells, but not to healthy normal cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>